STUDI LOKASI TITIK-TITIK RENTAN EROSI DI SEPANJANG JALAN SEKITAR BUKIT SELASIH SAMPAI KECAMATAN LUBUK KILANGAN - Astuti, Rina Febri Yani; Edial, Helfia; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
The aim of this study: Analyzing the level slope, land cover, rock types, soil types and analyze the existing level of rainfall at various points of erosion along the way Bukit selasih until Kecamatan Lubuk Kilangan. The research methodology is descriptive. Sampling technique based on geological maps Kecamatan Lubuk Kilangan the samples taken by the different rock types and is controlled by the degree of slope and land cover. The results showed that: the rate of slope at any point in the study sample was 35% in sample 1, sample 2 at 30% and 65% in sample 3, thus the third point of the sample had a high attrition rate because it has a steep slope up to very steep. Vegetation or land cover types that exist in the research area is planted with trees a little, shrubs, mosses and open. At each sample point there is always the possibility of erosion. On sample I (Indarung-Lubuk Paraku) with rock types Qf (Quarter fluvial) 5.5 rock hardness and condition weathered rock and soil texture being argillaceous sand, sample II (Lubuk Paraku-Panorama II) with Pcks rock type, rock hardness 8 and lightweight weathered rock conditions, which has the texture of clay soil are dusty and sample III (Panorama II-Lubuk-Selasih) Qtau rock types (Quarter andesites) which condition weathered rock, rock hardness level 2, and have a smooth texture that is loamy soil. In the study area has a high rainfall intensity at any time, the high levels of erosion due to high rainfall levels anyway.